2016
DOI: 10.1080/15592294.2016.1190895
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition has a pervasive impact on cardiac microRNA expression in isogenic mice

Abstract: The complex interaction between obesity, Western-style diets, and cardiovascular disease is of increasing interest, with a growing number of children being born to obese parents with poor lifestyle choices. These offspring have themselves an increased susceptibility to obesity and subsequent cardiovascular disease in adult life, which may be 'programmed' by their intrauterine environment. Cardiac microRNAs (miRNAs) are affected by multiple disease states, and have also been shown to be capable of exerting a ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 34 publications
0
12
0
1
Order By: Relevance
“…134 In this study, the comparison between prenatal exposure to maternal obesity and/or postnatal exposure to a Western diet on micro-RNA expression profiles showed that many more cardiac micro-RNA implicated in various cardiac pathologies 134 are altered in response to a relatively short period of postnatal overnutrition, rather than by a longer period of prenatal overnutrition. 134 Furthermore, cardiac micro-RNAs not only regulate functions, but also regulate metabolism at the body level. Indeed, miR-208 which cardiac levels are increased in high-fat diet mice, regulates the mediator complex subunit 13 (Med13) involved in the regulation energy balance in the heart.…”
Section: Micro-rnas Regulate Cardiac Development and Functionmentioning
confidence: 72%
“…134 In this study, the comparison between prenatal exposure to maternal obesity and/or postnatal exposure to a Western diet on micro-RNA expression profiles showed that many more cardiac micro-RNA implicated in various cardiac pathologies 134 are altered in response to a relatively short period of postnatal overnutrition, rather than by a longer period of prenatal overnutrition. 134 Furthermore, cardiac micro-RNAs not only regulate functions, but also regulate metabolism at the body level. Indeed, miR-208 which cardiac levels are increased in high-fat diet mice, regulates the mediator complex subunit 13 (Med13) involved in the regulation energy balance in the heart.…”
Section: Micro-rnas Regulate Cardiac Development and Functionmentioning
confidence: 72%
“…There is an intricate cardiac miRNA network, modulated by HFD administration, and implicated in the pathogenesis of CVD. Poor cardiac outcomes are linked to miRNAs modulated after HFD exposure in mice [ 56 ]. In young adult mouse offspring (12 weeks of age), exposure to maternal obesity altered some cardiac-relevant microRNA (miRNA, small, non-coding endogenous RNAs of 21–25 nucleotides) expression, overlaid on a cardiac miRNAome that was markedly changed after 9 weeks of exposure to a HFD (the HFD mimicked a Western fast-food diet) [ 56 ].…”
Section: High Fat Programming: Sex-specificity Altered Cardiac Gementioning
confidence: 99%
“…Poor cardiac outcomes are linked to miRNAs modulated after HFD exposure in mice [ 56 ]. In young adult mouse offspring (12 weeks of age), exposure to maternal obesity altered some cardiac-relevant microRNA (miRNA, small, non-coding endogenous RNAs of 21–25 nucleotides) expression, overlaid on a cardiac miRNAome that was markedly changed after 9 weeks of exposure to a HFD (the HFD mimicked a Western fast-food diet) [ 56 ]. After 9 weeks of the HFD administration, 33 cardiac miRNA expression profiles were altered [ 56 ].…”
Section: High Fat Programming: Sex-specificity Altered Cardiac Gementioning
confidence: 99%
See 1 more Smart Citation
“…В исследованиях на бабуинах, матери которых получали питание, богатое жирами, показана экспрессия микроРНК, вовлеченной в эпигенетическую регуляцию активности сердечно-сосудистой системы и метаболизма [61,62]. В других исследованиях, также проведенных на приматах, продемонстрировано существенное влияние подобного питания матери на метаболизм глюкозы и концентрацию инсулина в плазме крови потомства [63,64].…”
Section: повышенное питание матери и факторы риска развития кардиометunclassified